Restoration of Menstrual Fertility During Breastfeeding after Physiological Childbirth - Ochilova D. A.; Rakhmonkulova N.G (Genius Journals, 2022)
To this end, we studied the frequency and duration of lactational amenorrhea, the timing of the restoration of menstrual and fertile function in lactating women who underwent normal childbirth and cesarean section.For this purpose, we studied the frequency and duration of lactational amenorrhea, the timing of the restoration of menstrual and fertile function in lactating women who underwent normal childbirth and cesarean section.
Keywords: lactational amenorrhea; normal delivery and caesarean section